X-42=Y*2

Simple and best practice solution for X-42=Y*2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-42=Y*2 equation:


Simplifying
X + -42 = Y * 2

Reorder the terms:
-42 + X = Y * 2

Reorder the terms for easier multiplication:
-42 + X = 2Y

Solving
-42 + X = 2Y

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + X = 42 + 2Y

Combine like terms: -42 + 42 = 0
0 + X = 42 + 2Y
X = 42 + 2Y

Simplifying
X = 42 + 2Y

See similar equations:

| 15x-10=16x | | 16+40m= | | x-42=x*2 | | 42x-6=43x | | 18d-12v= | | -6x^2+6x+9=0 | | 7(2n+p)= | | -63+7x=12x-28 | | sin(3x)+sin(7x)=0 | | 5(h-4)=10 | | -6x^2+9x+9=0 | | 21z^2-70z+49= | | w-0.1=0.32 | | (8x+4)(5x+10)=0 | | 2x+5y=75 | | 5n+3=14-16 | | 3x+14y-8y+2-x= | | 2x(3x+3)=0 | | z^2+(1+i)z=4-7i | | z(4z+1)=0 | | 9x^2+90x+226=0 | | 40x^3-80x^2=0 | | -6+8m=-5+2m-1 | | ln(4x+5)=3 | | 3x^2-18x+30= | | 6t+60=12t | | 3x(9x-27)=0 | | 72=6(y-4)+2y+8y | | 0=-15+3x | | 8-7x-x^2=0 | | -2y+6=12 | | y=-15+3(0) |

Equations solver categories